Adoption intention of halal traceability system among agro-food SMEs / Nur Aminin Muhamad, Nitty Hirawaty Kamarulzaman and Nolila Mohd Nawi - Muhamad, Nur Aminin; Kamarulzaman, Nitty Hirawaty; Mohd Nawi, Nolila (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2019)
Traceability system enables agro-food small and medium enterprises (SMEs) to record the information about attributes of their products along the supply chain effectively. However, a huge concern arises among consumers regarding a violation of halal food products. Halal traceability system affirms that halalness should be retained across the supply chain. The adoption of the system in which the level of complexity is the same as the traceability system is still low despite the high usage of computers and the internet by most SMEs in Malaysia. This study aimed to determine the adoption intention level of halal traceability system among agro-food SMEs. A preliminary study was conducted on randomly selected 26 agro-food SMEs. Responses from agro-food SMEs were obtained through semi-structured interviews using a structured questionnaire. The data were analysed using several statistical analyses such as descriptive analysis, mean ranking analysis, and Chi-square analysis. The results revealed that most agro-food SMEs involved in this study (15 companies, 57.7%), were categorized as a small-sized company. Further, based on the mean ranking analysis, the results showed that agro-food SMEs have a low adoption intention of halal traceability system (mean score of 3.91). The results of Chisquare analysis revealed that there was a significant association between the size of the company and the adoption intention of halal traceability system among agro-food SMEs (p=0.073). This study concludes that more exposure to recent advances to agro-food SMEs in Malaysia will improve their adoption intention of halal traceability system.